Is Housing Growth Ever Inclusive Growth? Evidence from Three Decades of Housing Development in England and Wales, 1981–2011 - Tunstall, Rebecca (2020)
There is global concern about who gains from economic growth, including housing development, and global interest in making growth more inclusive. This article creates a new definition of ‘housing growth,’ growth in median space per person. It says that this housing growth is ‘inclusive’ if the worst-off make some gains, and ‘just’ if inequality does not increase. It applies these terms to data for 1981–2011 on rooms per person for England and Wales, the bulk of the UK, a nation with high income inequality but lower housing inequality. At national level, median housing space increased but the worst-off gained nothing, and inequality rose, so growth was neither inclusive nor just. Sub-national evidence shows that housing growth benefitted the worst-off in most areas, but they generally made very modest gains, and growth without increasing inequality was very rare. There was housing growth in all 10 regions except London, it was inclusive in 6 regions, but not just in any region. 97% of local authorities experienced housing growth, and it was inclusive in 72%, but the average gain for the worst-off was just 0.2 rooms/person over thirty years. Only 3% of local authorities achieved both inclusive and just growth. This suggests that in the UK and similar nations, local initiatives will be insufficient to achieve growth with significant gains for the worst-off, and that substantial change to the national system of housing development and allocation is needed. There may be a policy choice between benefitting the worst-off and reducing inequality. There is potential for further and comparative research.